2021
DOI: 10.1038/s41598-021-83967-7
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning based predictors for COVID-19 disease severity

Abstract: Predictors of the need for intensive care and mechanical ventilation can help healthcare systems in planning for surge capacity for COVID-19. We used socio-demographic data, clinical data, and blood panel profile data at the time of initial presentation to develop machine learning algorithms for predicting the need for intensive care and mechanical ventilation. Among the algorithms considered, the Random Forest classifier performed the best with $$\text {AUC} = 0.80$$ AUC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 16 publications
4
35
0
Order By: Relevance
“…This study also showed significant increased leukocyte count and decreased lymphocyte count in non-survivors [ 26 ]. ML was successfully applied to determine COVID-19 severity by predicting the need for ICU (AUC = 0.80) and the need for mechanical ventilation (AUC = 0.82) [ 27 ]. Random forest analysis showed that PCT, DD, CRP, respiratory rate, SpO2, albumin, AST/SGOT, calcium, influenza-like symptoms, and ALT/SGPT are the most important variables to predict the need for ICU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also showed significant increased leukocyte count and decreased lymphocyte count in non-survivors [ 26 ]. ML was successfully applied to determine COVID-19 severity by predicting the need for ICU (AUC = 0.80) and the need for mechanical ventilation (AUC = 0.82) [ 27 ]. Random forest analysis showed that PCT, DD, CRP, respiratory rate, SpO2, albumin, AST/SGOT, calcium, influenza-like symptoms, and ALT/SGPT are the most important variables to predict the need for ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Random forest analysis showed that PCT, DD, CRP, respiratory rate, SpO2, albumin, AST/SGOT, calcium, influenza-like symptoms, and ALT/SGPT are the most important variables to predict the need for ICU. Also, CRP, DD, PCT, SpO2, respiratory rate, creatinine, total protein, albumin, calcium, and age were the most important variables to predict the need for mechanical ventilation [ 27 ]. In a similar study, SpO2/FiO2, CRP, estimated glomerular filtration rate (eGFR), age, Charlson score, lymphocyte count, and PCT were the most important variables for the prediction COVID severity [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of diagnostic capability with machine learning, some recent studies have also been performed, but with smaller datasets, lack of temporal validation and often without clinical comparison 24 – 26 . More recently several machine learning based approaches have been published demonstrating more broader applicability in COVID-19 related applications including triage assessment 27 , severity classifcaiton 28 , 29 , risk prognostication including mortality 30 as well as applying to multi-omics data 31 . For example, a similar approach was tried with similar findings also with an attempt for explanability similar to our study 32 .…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, machine learning tools have been used for a variety of investigations, ranging from image analysis for diagnosis of SARS-CoV-2 pneumonia to predicting future pandemic waves [17]. These algorithms have the advantage of being able to combine a large amount of information, extracting the most predictive characteristics of the diagnosis associated with coronavirus disease [17,[21][22][23][25][26][27][28][29][30][31].…”
Section: Introduction 1contextmentioning
confidence: 99%
“…Therefore, during the COVID-19 pandemic, Machine Learning has been crucial in developing tools for a variety of investigations, ranging from image analysis for diagnosing SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2) pneumonia, predicting future pandemic waves, detecting multiple predictive and prognostic factors associated with increased severity of infection, to building severity models that help health systems prioritise care [8,[21][22][23][24][25][26][27][28][29][30].…”
Section: Introduction 1contextmentioning
confidence: 99%